Cuprous iodide nano material, preparation and application of cuprous iodide nano material in catalytic synthesis of N, N-dimethylacrylamide
Through the coordination reaction of copper salt and ammonia water in the preparation process of copper iodide, high-purity copper iodide nanosheets were generated, solving the problem of difficult control of the size of copper iodide crystals in the prior art, and achieving efficient application in nanoscale preparation and catalytic reactions.
Patent Information
- Application Number
- CN202411607985.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-07
AI Technical Summary
The prior art is difficult to effectively control the nanoscale preparation of cuprous iodide crystals, resulting in limited product performance and application, and the use of hydrazine hydrate as a reducing agent has safety and cost problems.
Copper salt and ammonia water are used as coordination agents to generate copper iodide nanosheets through heating reactions. Ammonia water is used as a gentle reaction medium, which reduces the reaction temperature and production cost and improves the purity and crystallinity of the product.
It has achieved efficient preparation of cuprous iodide nanosheets, with a high specific surface area and a unique two-dimensional structure, and is suitable for catalytic reactions, reducing the reaction temperature and occurrence of side reactions, and improving product conversion rate.
Smart Images

Figure CN119569102A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material preparation, and specifically relates to a cuprous iodide nanomaterial, a preparation method and application of the nanomaterial in catalytic synthesis of N,N-dimethylacrylamide. Background Art
[0002] Cuprous iodide has a wide range of uses and can be applied to organic synthesis catalysis, mixed gas separation and adsorption, artificial rainfall, feed and other fields. Cuprous iodide has three crystal phases: α, β, and γ. Changes in temperature will cause phase changes in CuI. The cuprous iodide crystal commonly referred to is the γ-CuI crystal. γ-CuI is a cubic p-type semiconductor material with a large direct energy gap (3.10 eV) and good anti-magnetism. The resistivity changes with the concentration of iodine ions. It is transparent in the visible light range and can be used as a solar cell material and a superconducting material. At the same time, γ-CuI is also a hole transport material with ultrafast luminescence properties at room temperature (collapse time is 90 ps). It is an inorganic scintillating material with the fastest known time response. It has unique advantages and potential application prospects in ultrafast scintillation measurement and is expected to play an important role in future ultrahigh count rate electron, γ-ray and X-ray measurements.
[0003] At present, the methods for preparing cuprous iodide mainly include laser pulse deposition, solvent method, liquid phase precipitation method, gamma ray irradiation technology, complexation and decomplexation method, and constant current electrolysis method. However, in the process of preparing cuprous iodide using the existing methods, large-sized cuprous iodide crystals are easily formed, making it difficult to control the crystal size to the nanometer scale, which greatly affects the performance and application of cuprous iodide products.
[0004] In order to effectively and accurately control crystal growth and solve the problem of agglomeration, Chinese patent CN 116768259A discloses a method for preparing cuprous iodide, which first mixes hydrazine hydrate with an iodine source to prepare an iodine-containing mixed solution, and then pumps the copper source and the iodine-containing mixed solution into a microreactor with the help of microfluidic reaction technology. After reacting at room temperature, nano cuprous iodide functional powder can be obtained. However, it is still worth noting that although this method realizes the controllable preparation of cuprous iodide at the nanoscale, it can avoid the secondary agglomeration of cuprous iodide grains during the preparation process, so that the product quality tends to be stable, but because hydrazine hydrate needs to be used as a reducing agent for reaction, there are still obstacles in the expansion of application, mainly because hydrazine hydrate is not only expensive, but also has strong alkalinity and high toxicity, and the production safety needs to be discussed; in addition, the cuprous iodide powder prepared according to this scheme is a nanoparticle with a particle size of 30-80nm, and the cuprous iodide nanoparticles are mainly used in the fields of organic synthesis and semiconductor materials. In view of the differences in the application fields of cuprous iodide nanomaterials with different morphologies, it is more appropriate to make cuprous iodide materials have better performance in the field of catalytic reactions. It is more appropriate to select a sheet-like cuprous iodide nanomaterial with a larger specific surface area. However, a very efficient and reasonable preparation scheme for cuprous iodide nanosheets has not yet been proposed in the prior art.
[0005] In summary, it is extremely necessary to propose a preparation scheme for cuprous iodide nanosheets with relatively low preparation cost, safer preparation process, easy operation, large output and high product uniformity. The proposal of the corresponding scheme can not only provide new ideas for the preparation of nanomaterials, but also provide more options for the field of catalytic reactions. Summary of the invention
[0006] The present invention solves the deficiencies in the prior art and provides a cuprous iodide nanomaterial and a preparation method thereof. The preparation process is simple and efficient, the reaction conditions are mild, the production safety is high, and the preparation cost is controlled. The invention is suitable for large-scale production and application. The prepared cuprous iodide nanomaterial is in the form of nanosheets and can be efficiently used in catalytic reactions.
[0007] In order to achieve the above technical objectives, the present invention is implemented by the following technical scheme: a method for preparing cuprous iodide nanomaterials, characterized in that it comprises the following steps:
[0008] 1) Weigh copper salt and ammonia water, dissolve them in water to form solution A, and then transfer them into a reaction kettle;
[0009] 2) adding ammonium iodide to solution A and heating the solution for reaction;
[0010] 3) Collecting the product, washing, filtering and drying it to obtain cuprous iodide nanosheets.
[0011] In the present application, ammonia water is used as a complexing agent to prepare cuprous iodide. The reaction equation involved in the preparation process is as follows:
[0012] (1)Cu 2+ +4NH3·H2O=[Cu(NH3)4] 2+ +4H2O;
[0013] (2)[Cu(NH3)4] 2+ +2I - =2CuI+4NH3.
[0014] Furthermore, the molar ratio of copper salt to ammonium iodide is 1:2-4; the ammonia water used is ammonia water with a mass concentration of 28%, and 1.5-3 mol of copper salt is added per liter of ammonia water.
[0015] Furthermore, the copper salt is any one of copper sulfate, copper nitrate, copper acetate and copper chloride.
[0016] Furthermore, in step 2), the heating process is carried out in a polytetrafluoroethylene-lined reactor, the heating reaction temperature is 150-200° C., and the reaction time is 5-50 hours.
[0017] Furthermore, in step 3), the drying temperature is 40-60° C. and the drying time is 3-6 hours.
[0018] The cuprous iodide nanomaterial prepared by the preparation method has a nanosheet structure, the thickness of the nanosheet is 15 to 25 nm, and the diameter of the nanosheet is 2 to 9 μm.
[0019] Based on the material properties, the above-mentioned cuprous iodide nanomaterial can be used in the catalytic cracking synthesis of N,N-dimethylacrylamide. Specifically, 3-(N,N-dimethylamino)-N,N-dimethylpropionamide is used as a raw material, cuprous iodide nanomaterial is used as a catalyst, and the amount of catalyst is 1.5-2.5% of the amount of the raw material. N,N-dimethylacrylamide (DMAA) can be efficiently synthesized at a catalytic reaction temperature of 180-240°C. DMAA is a fine chemical raw material with broad development and application prospects, and has broad application prospects in the fields of oil extraction, fine plastic modification, fine chemicals, life sciences, etc.
[0020] The beneficial effects of the present invention are:
[0021] 1. This application uses copper salt as a copper source and ammonium iodide as an iodine source to achieve the synthesis of γ-cuprous iodide nanosheets through a one-step chemical reaction in an ammonia system. The prepared cuprous iodide nanomaterial has high purity and good crystallinity;
[0022] 2. The present application uses ammonia water as a coordination agent, which first coordinates with copper ions to form cuprammonium ligands and then reacts with iodide ions to obtain γ-cuprous iodide. The reaction temperature only needs to be 150-200°C, the reaction process is mild, and ammonia water has low toxicity, a wide source, and a low price. The production equipment required for the production process is simple, easy to operate, and highly safe. The production cost is effectively controlled, which is conducive to the realization of industrial production;
[0023] 3. The γ-cuprous iodide prepared by the scheme disclosed in the present application is in the form of nanosheets, which have a larger specific surface area and a unique two-dimensional structure than cuprous iodide nanoparticles, and are suitable for application in the catalyst field. Using it as a catalyst for catalytic cracking of 3-(N,N-dimethylamino)-N,N-dimethylpropionamide to synthesize N,N-dimethylacrylamide can effectively improve the product conversion rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is an X-ray diffraction (XRD) spectrum of the cuprous iodide nanomaterial prepared in Example 1;
[0025] Figure 2 This is a scanning electron microscope (SEM) photograph of the cuprous iodide nanomaterial prepared in Example 1;
[0026] Figure 3 The small figures (a) and (b) are transmission electron microscope (TEM) and high-resolution transmission electron microscope (HRTEM) images of the cuprous iodide nanomaterial prepared in Example 1, respectively;
[0027] Figure 4 This is an X-ray diffraction (XRD) spectrum of the cuprous iodide nanomaterial prepared in Example 2;
[0028] Figure 5 This is a scanning electron microscope (SEM) photograph of the cuprous iodide nanomaterial prepared in Example 2. DETAILED DESCRIPTION
[0029] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the essence of the present invention, modifications and substitutions made to the methods, steps or conditions of the present invention all fall within the scope of the present invention.
[0030] This application uses a Japanese Rigaku D / max-γA X-ray powder diffraction (XRD) instrument to perform phase analysis on the samples. The graphite monochromator was used, the tube voltage and current were 40 kV and 40 mA respectively, and the scanning speed was 10.0 degrees per minute. The morphology and structure of the material were studied by transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM).
[0031] Example 1
[0032] 0.01 mol of copper sulfate and 5 mL of ammonia water (mass concentration of 28%) are placed in a beaker, 35 mL of distilled water is added to dissolve, and then transferred to a 50 mL polytetrafluoroethylene-lined reactor, 0.02 mol of ammonium iodide solid is added, and the mixture is sealed and placed in an electric constant temperature drying oven, and the temperature is raised from room temperature to 200° C. within 20 minutes, and the reaction is carried out at 200° C. for 5 hours, and the mixture is naturally cooled to room temperature. The final product in the reactor includes white sediment, and the white sediment adhered to the inner wall surface of the reactor needs to be collected together. All products are washed with distilled water and anhydrous ethanol for 3-5 times respectively, and samples are obtained after filtration. The samples are placed in a vacuum drying oven and dried at 50° C. for 4 hours to obtain cuprous iodide nanomaterials, with a yield of 80% and a product purity of 85%.
[0033] Figure 1 This is the X-ray diffraction spectrum of the cuprous iodide nanomaterial prepared in this example. Figure 1 From the X-ray diffraction spectrum (2θ at 20-80°), all diffraction peaks have high diffraction intensity and sharp peaks. All diffraction peaks can be calibrated as cubic phase cuprous iodide. The calculated lattice parameters This is consistent with the data reported in the literature (JCPDS no. 06-0246, ).
[0034] Observe the scanning electron microscope photo of the cuprous iodide nanomaterial prepared in this example ( Figure 2 ) It can be seen that the cuprous iodide nanomaterial prepared in this embodiment is a sheet-like material, the thickness of the nanosheet is about 20 nm, and the diameter of the nanosheet is about 2 to 9 μm.
[0035] From the transmission electron microscopy photograph of the cuprous iodide nanomaterial prepared in this example, it can be seen that the prepared cuprous iodide is a nano-sheet material with uneven thickness ( Figure 3 (a) small figure); further observe the high-resolution transmission electron microscope photo of the cuprous iodide nanomaterial prepared in this example ( Figure 3 In the middle (b) panel, clear lattice fringes can be seen, and the distance between adjacent fringes is 0.35 nanometers, which corresponds to the (111) crystal plane spacing of cuprous iodide, proving that the prepared nano-cuprous iodide has good crystallinity.
[0036] Example 2
[0037] 0.01 mol of copper nitrate and 5 mL of ammonia water (mass concentration of 28%) were placed in a beaker, 35 mL of distilled water was added to dissolve, and then transferred to a 50 mL polytetrafluoroethylene lined reactor, 0.02 mol of ammonium iodide solid was added, and the mixture was sealed and placed in an electric constant temperature drying oven, and the temperature was raised from room temperature to 200°C within 20 minutes, and the reaction was carried out at 200°C for 5 hours, and the mixture was naturally cooled to room temperature. The final product in the reactor included white sediment, and the white sediment adhered to the inner wall surface of the reactor was collected together, and all the products were washed with distilled water and anhydrous ethanol for 3-5 times respectively, and the samples were obtained after filtration, and the samples were placed in a vacuum drying oven and dried at 50°C for 4 hours to obtain cuprous iodide nanomaterials, with a yield of 82% and a product purity of 86%.
[0038] Observe the XRD spectrum of the cuprous iodide nanomaterial prepared in this embodiment ( Figure 4 ) and found that all the diffraction peaks in the spectrum corresponded to the diffraction peaks of cuprous iodide, proving that the prepared sample was a cubic phase of cuprous iodide material.
[0039] Observe the SEM photo of the cuprous iodide nanomaterial prepared in this example ( Figure 5 ) It can be clearly seen that the cuprous iodide prepared in this embodiment is also nanosheet-shaped, the average thickness of the cuprous iodide nanosheets is about 20 nanometers, and the nanosheets are only slightly aggregated.
[0040] Application Examples
[0041] The cuprous iodide nanosheets prepared in Example 1 were used as a catalyst to catalytically crack 3-(N,N-dimethylamino)-N,N-dimethylpropionamide (DMDA) to synthesize N,N-dimethylacrylamide (DMAA).
[0042] 5.00 g of 3-(N,N-dimethylamino)-N,N-dimethylpropionamide, 0.015 g of inhibitor 4010NA and 0.10 g of cuprous iodide nanosheets were weighed into a round-bottom flask. The temperature was controlled at 200° C. After reacting for 4 hours, DMAA was slowly distilled under reduced pressure to obtain DMAA. The mass fraction of DMAA was determined to be 44.6%.
[0043] In the prior art, the synthesis of DMAA by catalytic cracking of DMDA using a catalyst usually requires high temperature and low pressure conditions and long-term heating, and this processing technology is prone to cause side reactions such as product polymerization and coking. However, the catalytic reaction is carried out using the cuprous iodide nanosheets prepared in the present application as a catalyst. In view of the excellent catalytic properties of the cuprous iodide nanosheets, the reaction temperature can be reduced and long-term heating is not required. There are fewer side reactions in the product generation process, which not only reduces the difficulty of the reaction, but also improves the product conversion rate.
[0044] The above shows and describes the basic principles, main features and advantages of the present invention. However, the above is only a specific embodiment of the present invention, and the technical features of the present invention are not limited thereto. Any other implementation methods derived by any technician in the field without departing from the technical solution of the present invention should be included in the patent scope of the present invention.
Claims
1. A method for preparing a cuprous iodide nanomaterial, characterized in that: The steps include: 1) Weigh copper salt and ammonia water, dissolve them in water to form solution A, and then transfer them into a reaction kettle; 2) adding ammonium iodide to solution A and heating the solution for reaction; 3) Collecting the product, washing, filtering and drying it to obtain cuprous iodide nanomaterials.
2. The method for preparing a cuprous iodide nanomaterial according to claim 1, wherein: The molar ratio of copper salt to ammonium iodide is 1:2-4; the ammonia water used is ammonia water with a mass concentration of 28%, and 1.5-3 mol of copper salt is added to each liter of ammonia water.
3. The method for preparing a cuprous iodide nanomaterial according to claim 1, characterized in that: The copper salt is any one of copper sulfate, copper nitrate, copper acetate and copper chloride.
4. The method for preparing a cuprous iodide nanomaterial according to claim 1, wherein: In step 2), the heating process is carried out in a polytetrafluoroethylene-lined reactor, the heating reaction temperature is 150-200° C., and the reaction time is 5-50 hours.
5. The method for preparing a cuprous iodide nanomaterial according to claim 1, characterized in that: In step 3), the drying temperature is 40-60° C. and the drying time is 3-6 hours.
6. A cuprous iodide nanomaterial, characterized in that: The invention is prepared based on the preparation method described in any one of claims 1 to 5.
7. The cuprous iodide nanomaterial according to claim 6, characterized in that: The cuprous iodide nanomaterial is in the form of nanosheets, the thickness of the nanosheets is 15 to 25 nm, and the diameter of the nanosheets is 2 to 9 μm.
8. The use of the cuprous iodide nanomaterial as claimed in claim 6 in the catalytic cracking synthesis of N,N-dimethylacrylamide, characterized in that: The catalytic reaction uses 3-(N,N-dimethylamino)-N,N-dimethylpropionamide as a raw material and the cuprous iodide nanomaterial as a catalyst to synthesize N,N-dimethylacrylamide.
9. The use according to claim 8, characterized in that The amount of catalyst used is 1.5-2.5% of the amount of raw materials used, and the catalytic reaction temperature is 180-240°C.
Citation Information
Patent Citations
Preparation method of nano cuprous iodide
CN116768259A